Quantifying multiphase SEI growth in sulfide solid electrolytes - Alt, Christoph D.; Müller, Nadia U.C.B.; Riegger, Luise M.; Aktekin, Burak; Minnmann, Philip; Peppler, Klaus; Janek, Jürgen; Justus Liebig University Giessen (My University, 2024)
The incorporation of lithium metal anodes in solid-state batteries (SSBs) is impeded due to the chemical reduction of sulfide solid electrolytes (SEs) in contact with lithium metal. Growth mode, composition, and microstructure of a few model-type SE interphases (SEIs) are slowly unveiled. The objective of this study is to better understand the transport properties of typical multiphase SEIs by direct reaction of the SE with lithium metal powder. Hence, the composition and conduction properties (σion and σel) of synthesized bulk-scale SEI-type material (of Li6PS5Cl) are analyzed. The kinetic predictions using a Wagner-type diffusion model align well with recent results of electrochemical studies on cell-level multiphase SEIs. Accordingly, these findings enhance the ability to model transport parameters with greater accuracy and contribute to a deeper understanding of SEI growth and kinetics in SSBs. The need to stabilize the Li|SE interface by controlling the partial conductivities of the resulting SEI is emphasized.
Keywords: ddc:540